ANALISIS KESULITAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI UPTD SD INPRES MATAP - Veni Viktoria Mauro; Nehemia Fanpada; Imanuel Y.H Manapa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study was to analyze teachers' difficulties in implementing the Merdeka Curriculum at the UPTD SD Inpres Matap and to identify the factors hindering teachers in implementing the Merdeka Curriculum at the UPTD SD Inpres Matap. The focus of the study was teachers' difficulties in implementing the Merdeka Curriculum at the UPTD SD Inpres Matap. This study used a qualitative approach with descriptive methods. Data collection techniques were conducted through observation, interviews, and documentation. The subjects were homeroom teachers of grades I, II, III, V, and VI at the UPTD SD Inpres Matap. The researchers used five indicators to conduct the study, including understanding the merdeka Curriculum, teaching materials, facilities and infrastructure, learning implementation, and evaluation.The results showed that teachers still experience difficulties in implementing the Merdeka Curriculum. These difficulties include difficulty in compiling teaching modules, reducing CP to TP, adapting learning to student characteristics, limited facilities and infrastructure, a lack of learning resources, and limited use of learning technology. Furthermore, the implementation of authentic assessment, projects, and portfolios has not been fully optimized, especially in lower grades. To overcome these obstacles, teachers collaborate, discuss, exchange ideas, and utilize facilities and the surrounding environment as learning resources. Therefore, support is needed in the form of training, mentoring, additional facilities and infrastructure, and increased teacher understanding so that the implementation of the Independent Curriculum can be more effective and tailored to student needs.